Endoscopy for GSp(4) and the Cohomology of Siegel Modular Threefolds - Weissauer, Rainer (Lecture notes in mathematics, 2009)
An Application of the Hard Lefschetz Theorem -- CAP-Localization -- The Ramanujan Conjecture for Genus two Siegel modular Forms -- Character identities and Galois representations related to the group GSp(4) -- Local and Global Endoscopy for GSp(4) -- A special Case of the Fundamental Lemma I -- A special Case of the Fundamental Lemma II -- The Langlands-Shelstad transfer factor -- Fundamental lemma (twisted case) -- Reduction to unit elements -- Appendix on Galois cohomology -- Appendix on Double Cosets
Includes bibliographical references (p. 355-359) and index
Keywords: Spurformel; Kohomologiegruppe; Siegel-Modulform